Analysis of Performance Characteristics and Development Overview of US Navy AIM-174B Very Long-Range Air-to-Air Missile - Chen Li, Tian Hao, Yuan Cheng, Zheng Ke (Hangkong bingqi)
AIM-174B is a new very long-range air-to-air missile developed by the US Navy based on the RIM-174 "Standard-6" surface-to-air missile, it is also the air-to-air missile with the longest range ever equipped by US Air Force/Navy combat aircraft.On the basis of a detailed analysis of the development background of AIM-174B, this article comprehensively evaluates and judges its main performance characteristics, the enhancement of combat capabilities brought to the US Navy, and the main performance deficiencies that exist.Finally, this article provides a brief introduction and outlook on the research and development progress of AIM-174B, as well as its future application prospects.